(untitled) - Huỳnh, Thị Thanh Trúc (Can Tho, 2009)
The purpose of the study was to evaluation to what extent listening strategy training affects the listening comprehension of non-English major student. It was hypothesized that the participants listening comprehension would be enhanced through the strategy instruction.
Keywords: English language,English language; Problems, exercises, etc,Study and teaching